Metabolic changes of thalamus assessed by 1H-MRS spectroscopy in patients of cervical spondylotic myelopathy following decompression surgery - Jiangqin Zheng; Yujin Zhang; Baogen Zhao; Ning Wang; Ting Gao; Li Zhang (Frontiers in Neurology)
ObjectiveTo assess the changes of thalamic metabolites before and after surgery in patients with Cervical Spondylotic Myelopathy (CSM) using Hydrogen Proton Magnetic Resonance Spectroscopy (1H-MRS) and to investigate its association with improvement in neurological function.MethodsForty-eight CSM patients who underwent cervical decompression surgery from December 2022 to June 2023 were included, and 33 healthy volunteers were recruited. All subjects underwent bilateral thalamic 1H-MRS scans before the surgical procedure, and subsequently again 6 months later. Neurological function was assessed pre-operatively and post-operatively (6 months) in all patients with CSM using the modified Japanese Orthopedic Association (mJOA). The changes of mJOA (ΔmJOA = postoperative mJOA–preoperative mJOA) were employed as an indicator of neurological improvement. The pre- and postoperative metabolic ratio of N-acetylaspartate/creatine (NAA/Cr), choline/creatine (Cho/Cr), myo-inositol/creatine (mI/Cr), glutamate and glutamine complex/creatine (Glx/Cr) were statistically compared in CSM patients and healthy controls (HCs). A correlation analysis was conducted to determine the relationship between alterations in pre- and postoperative metabolite ratios (ΔNAA/Cr, ΔCho/Cr, ΔmI/Cr, ΔGlx/Cr) and ΔmJOA.ResultsCompared to the HCs, patients with CSM showed significantly lower pre- and post-operative NAA/Cr (Z = −4.235, p < 0.001; Z = −3.184, p = 0.001), Cho/Cr (Z = −5.050, p < 0.001; (Z = −2.624, p = 0.007) and mI/Cr (Z = −3.739, p = 0.001; Z = −2.014, p = 0.044). There was no difference in Glx/Cr between patients in patients with CSM, either preoperatively or postoperatively, compared to HCs. Post-operative NAA/Cr (Z  = −2.285, p = 0.041) and mI/Cr (Z = −2.925, p = 0.021) were increased in CSM patients compared to pre-operative NAA/Cr and mI/Cr. In CSM patients, ΔmI/Cr correlated significantly with ΔmJOA (r = 0.507, p < 0.001).ConclusionThe preliminary findings indicate that metabolites in the thalamus of CSM patients exhibit changes following surgery. Additionally, it has been demonstrated that elevated postoperative mI correlates with improvements in neurological function.